2011
DOI: 10.1186/1477-5956-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the proteome of human airway epithelial secretions

Abstract: BackgroundAirway surface liquid, often referred to as mucus, is a thin layer of fluid covering the luminal surface that plays an important defensive role against foreign particles and chemicals entering the lungs. Airway mucus contains various macromolecules, the most abundant being mucin glycoproteins, which contribute to its defensive function. Airway epithelial cells cultured in vitro secrete mucins and nonmucin proteins from their apical surface that mimics mucus production in vivo. The current study was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 49 publications
(54 reference statements)
4
51
0
Order By: Relevance
“…Later, Ali et al [19] identified 56 proteins in a "mucin" fraction isolated under physiological conditions from primary human tracheobronchial epithelial cells grown in air/liquid interface, supporting the previous report [11] that airway mucins are tightly associated with various molecules. Proteomic analysis of the 56 proteins included not only mucins but also many functionally active proteins, including antimicrobial, anti-proteolytic, anti-oxidative, and anti-inflammatory proteins [19]. This finding is highly significant because it had been thought that the complex structure of "mucins" itself was responsible for their multifaceted properties that are necessary for host defense against inhaled harmful substances, including anti-microbial, anti-proteolytic, and anti-oxidative activities [20].…”
Section: Mucins Are "Aircraft Carriers" In the Airway Surface Fluidsupporting
confidence: 53%
See 1 more Smart Citation
“…Later, Ali et al [19] identified 56 proteins in a "mucin" fraction isolated under physiological conditions from primary human tracheobronchial epithelial cells grown in air/liquid interface, supporting the previous report [11] that airway mucins are tightly associated with various molecules. Proteomic analysis of the 56 proteins included not only mucins but also many functionally active proteins, including antimicrobial, anti-proteolytic, anti-oxidative, and anti-inflammatory proteins [19]. This finding is highly significant because it had been thought that the complex structure of "mucins" itself was responsible for their multifaceted properties that are necessary for host defense against inhaled harmful substances, including anti-microbial, anti-proteolytic, and anti-oxidative activities [20].…”
Section: Mucins Are "Aircraft Carriers" In the Airway Surface Fluidsupporting
confidence: 53%
“…Later, Ali et al [19] identified 56 proteins in a "mucin" fraction isolated under physiological conditions from primary human tracheobronchial epithelial cells grown in air/liquid interface, supporting the previous report [11] that airway mucins are tightly associated with various molecules. Proteomic analysis of the 56 proteins included not only mucins but also many functionally active proteins, including antimicrobial, anti-proteolytic, anti-oxidative, and anti-inflammatory proteins [19].…”
Section: Mucins Are "Aircraft Carriers" In the Airway Surface Fluidmentioning
confidence: 50%
“…8, A and B). Again, given the dilutional effect inherent to the BAL procedure, combined with the known sequestration of a fraction of MUC1-ED within the fluid lining the bronchoalveolar compartment (38), these data likely underestimate the true levels of shed MUC1-ED in the BALF from P. aeruginosa-colonized patients.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Recent shotgun proteomics reports revealed large catalogues of exoproteomes of several bacteria [11,12] and fungi [13] comprising a large list of items unsuspected from prior 2D-gel based studies. Regarding human proteomes, a large panel of secretomes have been described from myeloid cells [14], dendritic cells [15], stem cells [16], endothelial cells [17], astrocytes [18], and airway epithelial cells [19]. The description of specific cancer biomarkers being the aim of most secretome studies, more than 28 reports presented the catalogue of secreted proteins from cancer cell lines [5].…”
Section: Introductionmentioning
confidence: 99%